Adubação nitrogenada antecipada no algodoeiro em solo arenoso - Silva, Gustavo Ricardo Aguiar (2023)
One of the major challenges in agriculture is to improve the efficiency of nitrogen use by crops, because its rapid transformation easily exposes it to losses by volatilization and leaching. Thus, the objective was to evaluate the effect of nitrogen fertilization management (sources and times of application) on nitrogen (N) content in soil and plant, productivity and quality of cotton fibers in a sandy soil. The experiment was conducted at the Experimental Farm of UNOESTE, in Presidente Bernardes-SP, in the 2020/21 and 2021/22 season. The soil of the area is sandy in texture. The experimental design was in randomized blocks with five replications. The plots were 7 meters long and 3.6 meters wide and composed of the following treatments: 1 - Ammonium nitrate applied to launch at 20, 40 and 60 days after emergence (DAE) (AN); 2 - Conventional urea applied to pitch at 20, 40 and 60 DAE (U); 3 - Conventional urea applied 100% to the 30 DAE in an incorporated form (U 30 DAE); 4 - Controlled release urea with 70% of the rate applied in the sowing of incorporated form and 30% with conventional urea at 50 DAE (CRU/U); 5 - Controlled release urea with 70% of the rate applied in the sowing of incorporated form and 30% at 50 DAE (CRU 70/30); 6 - Controlled release urea applied 100% in the sowing of incorporated form (CRU 100 I); 7 - Controlled release urea applied broadcasted 100% at sowing (CRU 100 B). In the 2020/21 season there was no effect of the treatments on the variables analyzed, in the 2021/22 crop, fiber yield, number of weeds and average weight of weeds were higher in treatments with CRU/U, CRU 70/30 and CRU 100 B. The accumulation of productivity per node in the 2021/22 crop shows that the effect of treatments began to be evidenced from the 17th fruit branch. In the same season, the N content in the leaf, leaf area index (LAI) and fiber quality, except for the short fiber index, showed no difference among treatments. The index of short fibers decreased (2021/22) in treatments with CRU 100 L and U 30 DAE. The productivity of the treatments was higher in the second season, mainly in treatments with CRU 100 B, CRU 70/30, CRU/U and NA. The managements with CRU 100 B, CRU 70/30 and CRU/U increase ammonia contents in the most superficial layers (0-40 cm) and reduce N mobility in nitric form in the deepest layers (0.4 – 0.8 m). In smaller cycles of cultivation (2020/21), a single application in sowing with ULC brings benefits to cotton productivity without affecting fiber quality. In larger cycles (2021/22), the best fertilization strategies are with CRU/U, CRU 70/30 and CRU 100 B.